Intra-regional mobility of PhD students in the European Union: the outcomes of region-making policy?. Issue 2 (3rd July 2022) - Mathies, Charles; Cantwell, Brendan
ABSTRACT: This paper examines the flow of intra-European Union (EU) students for doctoral (PhD) studies to identify reasons for differences in international student mobility and migration (ISM) among member states. Rather than conceptualising intra-EU PhD student ISM only through push–pull forces, we theorise the intra-EU PhD ISM is associated with relative levels of national resources or levels of capital. We investigate the intra-EU PhD ISM through dyadic country pairings allowing the use of Gravity models to estimate the effect of variables associated with stocks of capital ascribed to a country to the change in the number of PhD students. The findings of this study indicate while there is asymmetry among EU member states, investment in strengthening the higher education systems within individual EU countries can strengthen the overall cohesion and competitiveness of the EU in the global science competition. Thus, policy focused on enhancing developing national higher education systems can pay dividends throughout the EU.